Formation of graphene oxide gel via the π-stacked supramolecular self-assembly - Shi, Nai-En (2013)
Graphene oxide gel (GOG) possesses intrinsic three-dimensional (3D) networking architecture with large surface area and high porosity. Here, we report a novel method of fabrication of GOG by self-assembling a ferrocene-decorated graphene oxide sheets (GOS) at room temperature. Our systematic investigations reveal that Fc plays a critical role in the formation of such unique 3D architecture, as it functions as an effective interlayer cross-linker through the π–π interaction. The morphology, crystal structure, chemical bonding, porosity and thermal stability of the as-prepared GOG have been studied. This work successfully provides a facile and efficient way to form GOG and will extend the potentials of GOG as a promising electro-active material in carbon-based electronics or catalytic reactors.